Perchlorination of Coronene Enhances its Propensity for Self‐Assembly on Graphene. Issue 3 (23rd December 2015) - Conti, Simone; del Rosso, Maria G.; Ciesielski, Artur; Weippert, Jürgen; Böttcher, Artur; Shin, Yuyoung; Melinte, Georgian; Ersen, Ovidiu; Casiraghi, Cinzia; Feng, Xinliang; Müllen, Klaus; Kappes, Manfred M.; et al.
Abstract: Providing a quantitative understanding of the thermodynamics involved in molecular adsorption and self‐assembly at a nanostructured carbon material is of fundamental importance and finds outstanding applications in the graphene era. Here, we study the effect of edge perchlorination of coronene, which is a prototypical polyaromatic hydrocarbon, on the binding affinity for the basal planes of graphite. First, by comparing the desorption barrier of hydrogenated versus perchlorinated coronene measured by temperature‐programmed desorption, we quantify the enhancement of the strength of physisorption at the single‐molecule level though chlorine substitution. Then, by a thermodynamic analysis of the corresponding monolayers based on force‐field calculations and statistical mechanics, we show that perchlorination decreases the free energy of self‐assembly, not only enthalpically (by enhancing the strength of surface binding), but also entropically (by decreasing the surface concentration). The functional advantage of a chemically modulated 2D self‐assembly is demonstrated in the context of the molecule‐assisted liquid‐phase exfoliation of graphite into graphene. Abstract : Leading edge of self‐assembly : We demonstrate that the chemical functionalization of coronene by perchlorination significantly enhances its propensity to form a self‐assembled monolayer on graphene, not only by increasing the strength of surface binding, but also by reducing the entropy cost of covering a given surface area.